The Effect of Fiscal Policy on Economic Inequality and Sustainable Development in ASEAN - Anwar, Syaiful (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This study analyzes the influence of fiscal policy on economic inequality and sustainable development in ASEAN (Association of Southeast Asian Nations). Through data and narrative analysis, we see that fiscal policy plays an important role in shaping economic conditions in ASEAN countries. Prudent and effective fiscal policies can reduce economic inequality, promote inclusive growth, and achieve sustainable development. However, ASEAN countries are faced with challenges in managing fiscal policy, such as institutional capacity that needs to be improved and complex regional policy harmonization. In the face of these challenges, there are important opportunities through regional cooperation, exchange of experiences, and capacity building. To achieve inclusive and sustainable growth, it is important for ASEAN countries to strengthen their institutional capabilities, enhance regional coordination, and capitalize on collaboration opportunities.